Purification and Chemistry of Bacteriophage ϰ - Schade, Sylvia Z. (1967)
From a stock of ϰ phage grown on Salmonella, a host-range mutant which attacks Escherichia coli was isolated. As in the case of Salmonella, only motile strains of E. coli are sensitive to ϰ. The phage shows an eclipse period of 35 min and a minimal latent period of 52 min. The adsorption rate constant is 3 × 10(−9) ml/min. Adsorption shows a marked dependence on temperature. Bacteriophage ϰ was purified by differential centrifugation and CsCl density gradient centrifugation. It contains deoxyribonucleic acid (DNA) which is double-stranded. The DNA has a molecular weight of 42 million and a guanine plus cytosine content of 57%. Of 68 molecules of DNA inspected, 7 were circular. The phage particle weight is about 90 million.